2016
DOI: 10.1007/s10792-016-0261-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foveal photoreceptor layer in eyes with macular edema associated with branch retinal vein occlusion after ozurdex treatment

Abstract: The aim of this study was to evaluate the central retinal thickness (CRT), outer nuclear layer thickness (ONLT), photoreceptor layer thickness (PLT), photoreceptor layer integrity, and the correlation between visual acuity and PLT in eyes with branch retinal vein occlusion (BRVO) 2 months after treatment with intravitreal dexamethasone implant (Ozurdex; Allergan, Inc, Irvine, CA). In this prospective study, 32 eyes of 32 patients were enrolled. A single injection of Ozurdex was administered to all the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Another reason may be the longer period of oedema in RNB (4.1 months) compared to DEX (2.6 months). Also, outer nuclear layer thickness was reported to be more closely correlated with vision rather than CRT . Moreover, in ischaemic BRVO resolution of macular oedema with treatment may not result in visual improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason may be the longer period of oedema in RNB (4.1 months) compared to DEX (2.6 months). Also, outer nuclear layer thickness was reported to be more closely correlated with vision rather than CRT . Moreover, in ischaemic BRVO resolution of macular oedema with treatment may not result in visual improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The normal function of the foveal photoreceptor layer may well be necessary to regain good visual function. Therefore, some researchers tried to measure the thickness of various retinal layers, in order to lay a theoretical foundation for the visual recovery of patients with macular edema [ 4 , 5 , 10 ]. In this study, we evaluated the change in various retinal layers' thickness in BRVO after conbercept injection and analyzed the correlation between them and BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…Although, retinal thickness has been reduced to physiological levels successfully after regression of macular edema, the loss of photoreceptor cells may lead to limited visual recovery. Altunel et al [ 4 ] and Ota et al [ 5 ] showed that there was no correlation between CFT and BCVA after treatment. The outcome of our study in correlation between BCVA and CFT with conbercept treatment is similar to theirs.…”
Section: Discussionmentioning
confidence: 99%
“…The photoreceptor outer segment is thinner in patients with diabetic macular edema compared to the controls or patients with DR without macular edema [15]. In eyes with macular edema secondary to RVO, the photoreceptor layer thickness is associated with visual function [16]. Furthermore, photoreceptor loss occurs in AMD [17].…”
Section: Discussionmentioning
confidence: 99%